UJI DAYA KECAMBAH BENIH AREN (Arenga pinnata MERR.) - Hadi Rosadi; Damaris Payung; Dina Naemah (Jurnal Sylva Scienteae, 2020)
Aren tree (Arenga Pinnata Merr.) Is one of the palm trees that is almost spread throughout Indonesia and is one type of plant that has a high economic value for it needed a good way of plant propagation to get the quality we need, the propagation of palm trees only can be through the seeds so it takes preliminary treatment techniques. Techniques to accelerate germination aren feels unsatisfactory because the techniques that have been developed are still quite difficult so that the research using simple preliminary treatment and it is the answer of the difficulty of germination seeds aren. The techniques used are also simple as well as thinking, drilling, sanding and soaking the palm seeds. The purpose of this research is to know the power of seed sprouts. This research was conducted in November 2017 until February 2018 at Silvicultural Laboratory II of Faculty of Forestry Universitas Lambung Mangkurat Banjarbaru. This research used sand planting medium and had 3 different preliminary treatment on the seeds of seed (A) = Seed soaked in water with time ± 6 hours and applied to all treatment as originally, treatment (B) = abrasive using sandpaper with size roughness 80 and treatment (C) = Soak in hot water for 10 minutes at 100 ℃. The results showed the highest germination on treatment B with 65% sprout value of 20 seeds that have been tested and the results of observations that have been implemented within 90 days.Keywords: Arenga pinnata; germination; sanding; soak